Risk Analysis Of The Use Of Transactions Digital Cryptocurrency As Investment In Prespective Islam On Gen Z In Central Sumatra - Ary Dean Amri; Jaka Saputra; Ilham Hanafi; Mela Yolanda; Harpeni .; Saputri . (JOURNAL OF SHARIA ECONOMICS, 2023)
This study aims to understand the views of Generation Z regarding risk of trust and security of the digital capital market on the island of Sumatra, as well see investment market capital IDX in perspective economy Islam. Method the research used is quantitative research using data primary from completed questionnaire tested for validity and reliability, as well data secondary from various related print and electronic media. Data analysis was performed with simple regression test and multiple regression test using SPSS. Results testing shows that the factor of safety (X2), which involves a factor social, culture, marketing, And election investment sharia, more dominant compared to factor trust (X1), like factor personal, psychology, And economic factor. However, neither trust (X1) nor security (X2) have positive and significant influence on the risk of stock (Y) Generation Z on the Island Sumatra. In order to increase the understanding and prudence of Generation Z in investing digitally, it is important for them to understand the legal aspects and logical (2L) as well as aspect returns (yield results) And risk (risk) (2R) before use application investment. With notice management risk, Generation Z can choose good investments and fulfill financial obligations period front they. Study This give outlook about perception Generation Z towards digital capital markets and deep Islamic economic perspectives investment IDX capital market in Sumatra island.